SelfSplit parallelization for mixed-integer linear programming - Fischetti, Matteo; Monaci, Michele; Salvagnin, Domenico (Computers & operations research, 2018)
•SelfSplit an easy-to-implement way to parallelize a sequential tree-search code.•SelfSplit is deterministic and requires (almost) no communication among workers.•We investigate the performance of SelfSplit when applied to a MILP solver.•Both ad-hoc and general purpose MILP solvers are considered.•Computational results show that good speedups can be achieved in the MILP context. SelfSplit is a simple static mechanism to convert a sequential tree-search code into a parallel one. In this paradigm, tree-search is distributed among a set of identical workers, each of which is able to autonomously determine—without any communication with the other workers—the job parts it has to process. SelfSplit already proved quite effective in parallelizing Constraint Programming solvers. In the present paper we investigate the performance of SelfSplit when applied to a Mixed-Integer Linear Programming (MILP) solver. Both ad-hoc and general purpose MILP codes have been considered. Computational results show that SelfSplit, in spite of its simplicity, can achieve good speedups even in the MILP context.